Effects of Powdery Mildew on 1000-Kernel Weight, Crude Protein Content and Yield of Winter Wheat in Three Consecutive Growing Seasons - Xue-ren CAO; Dong-ming YAO; Xia-yu DUAN; Wei LIU; Jie-ru FAN; Ke-jian DING; Yi-lin ZHOU (Journal of Integrative Agriculture, 2014)
In order to clarify the impact posed by wheat powdery mildew (Blumeria graminis f. sp. tritici) on the yield and yield components in different epidemic seasons, field trials were conducted in three growing seasons, 2009–2010, 2010–2011 and 2011–2012, in Langfang City, Hebei Province, China. The relationships between 1000-kernel weight, crude protein content of grain and yield and disease index (DI), as well as area under disease progress curve (AUDPC) were studied. The models of the percentage of loss of 1000-kernel weight, crude protein content and yield were constructed using DI at critical point (CP) of growth stages (GS) and AUDPC in the three growing seasons, respectively. The CPs for estimating 1000-kernel weight, crude protein content of grain and yield of wheat caused by powdery mildew were GS 11.1, GS 10.5.3 and GS 10.5.3, respectively. Models based on DI at CP to estimate the percentage of loss of 1000-kernel weight, crude protein content of grain and yield were better than models based on AUDPC. And models of the percentage of loss of 1000-kernel weight, crude protein content and yield for 2011–2012 season were significant different from these for 2009–2010 and 2010–2011 seasons. These results indicated that besides powdery mildew, weather conditions also had influence on 1000-kernel weight, crude protein content of grain and yield loss of wheat when powdery mildew occurred.